Penggunaan Hasil Penilaian Pendidikan dalam Pengembangan Program Belajar - Ryan Ferdinand, Mustofa; Aziz Afifissina, Nur; Nur Putri Wulandari, Andi; Anisah Taqiyah, Siti; Quratu Aini, Asma’ (CV Kalimasada Group, 2024)
Educational assessment is an important component in the learning process. The assessment results can be used for various purposes, one of which is developing learning programs. By analyzing assessment results, teachers can find out students' strengths and weaknesses, as well as identify learning materials that need to be improved. This can help teachers in preparing learning programs that are more effective and suit the needs of students. Assessment is a teacher's activity related to making decisions regarding student learning outcomes that reflect the achievement of competencies during a particular learning process. Assessment is carried out holistically regarding aspects of knowledge, attitudes and skills for each level of education, both during learning (process assessment) and after learning has been carried out (learning outcomes assessment).